2016
DOI: 10.1007/s10803-016-2895-1
|View full text |Cite
|
Sign up to set email alerts
|

Judgment of Learning Accuracy in High-functioning Adolescents and Adults with Autism Spectrum Disorder

Abstract: This study explored whether adults and adolescents with autism spectrum disorder (ASD) demonstrate difficulties making metacognitive judgments, specifically judgments of learning. Across two experiments, the study examined whether individuals with ASD could accurately judge whether they had learnt a piece of information (in this case word pairs). In Experiment 1, adults with ASD demonstrated typical accuracy on a standard ‘cue-alone’ judgment of learning (JOL) task, compared to age- and IQ-matched neurotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Studies have not consistently observed a difference in metamemory “judgements of learning” in ASD (Grainger et al, 2016 ; Wojcik et al, 2014 ), thus questioning the full extent of reduced subjective awareness and its relation to recollection in this population. Although it is possible that parietal dysfunction plays some role in recollective experience in ASD, a clear area of divergence between parietal patients and people with ASD is that the former tend not to show any changes in objective source memory (e.g., Simons et al, 2010 ).…”
Section: Neurocognitive Accounts Of Recollection In Asdmentioning
confidence: 93%
“…Studies have not consistently observed a difference in metamemory “judgements of learning” in ASD (Grainger et al, 2016 ; Wojcik et al, 2014 ), thus questioning the full extent of reduced subjective awareness and its relation to recollection in this population. Although it is possible that parietal dysfunction plays some role in recollective experience in ASD, a clear area of divergence between parietal patients and people with ASD is that the former tend not to show any changes in objective source memory (e.g., Simons et al, 2010 ).…”
Section: Neurocognitive Accounts Of Recollection In Asdmentioning
confidence: 93%
“…First, estimating an effect size for group differences in key dependent variables was a challenge. There is little previous research on metacognitive monitoring in ASD and existing studies have used a variety of tasks that are arguably not directly comparable (e.g., Cooper, Plaisted-Grant, Baron-Cohen, & Simons, 2016 ; Grainger, Williams, & Lind, 2016a , 2016b ; Nicholson et al, 2019 ; Williams, Bergström, & Grainger, 2018 ; Williams & Happé, 2010 ; Williams & Happé, 2009 ; Wilkinson, Best, Minshew, & Strauss, 2010 ; Wojcik, Allen, Brown, & Souchay, 2011 ; Wojcik et al, 2014 ), so basing an effect size on the weighted effect size across previous studies was inappropriate, in our view. Second, we predicted a null effect for the between-groups difference in gambling accuracy, which makes estimating “sufficient power” difficult.…”
Section: Methodsmentioning
confidence: 99%
“…reality monitoring and feeling-of-knowing), whereas others have found this population to be comparable to children without autism (e.g. judgment of learning; Cooper, Plaisted-Grant, Baron-Cohen, & Simons, 2016;Grainger, Williams, & Lind, 2014;Grainger, Williams, & Lind, 2016b).…”
Section: Adhdmentioning
confidence: 92%